PLANNING OF ROOFTOP SOLAR POWER PLANTS FOR INTEGRATED CLASSROOM AND LABORATORY BUILDINGS, SILIWANGI UNIVERSITY CAMPUS I - Faridah, Linda; Muhammad Rasul Ja’fari; Usrah, Ifkar (KURVATEK, 2025)
The need for electrical energy in Indonesia is increasing, while dependence on fossil fuels remains dominant. One potential alternative is the utilization of solar energy through rooftop Solar Power Plants (PLTS). This study aims to design a rooftop PLTS system in the Integrated Classroom and Laboratory Building, Campus 1, Siliwangi University with a technical and economic approach. The research method includes collecting data on load profiles and potential solar radiation, designing system capacity, selecting main components, and simulating using PVsyst software to obtain estimates of energy production and system performance. The planning results show a design capacity of 71,107 Wp with a configuration of 118 solar panels with a capacity of 600 Wp, which produces energy production of around 299–318 kWh per day or equivalent to 109–116 MWh per year. The PVsyst simulation produces an average Performance Ratio value of around 80%, which is in the good category. However, the economic analysis using the Net Present Value (NPV) method shows a negative value (−996,310,000), so this project is not yet financially feasible if implemented in a fully off-grid scenario. In conclusion, the implementation of rooftop solar power plants in the Integrated Classroom and Laboratory Building, Campus 1, Siliwangi University is technically feasible, but not yet financially feasible under current conditions. Therefore, it is recommended to implement a hybrid or on-grid scenario, as well as an electricity tariff sensitivity analysis to increase economic feasibility.